Antiparkinson Medication In Ageing Population: Trends And Challenges - Lakshmi , G. Anantha; Bhatta , Rahul Kumar; Adnanuddin , Mohammad; Gavini, Esha Reddy; Shadan, Shadan; Reddy , C. Rajesh (Journal of Neonatal Surgery, 2025)
Parkinson's disease (PD) is a progressive neurodegenerative disorder that predominantly affects the elderly, causing motor and non-motor symptoms that diminish quality of life. A prospective observational study in a tertiary care hospital examined prescription patterns, medication adherence, and challenges in managing PD among patients aged 60 and above. The study involved 50 participants, 68%of whom were male, with the highest representation (40%) in the 66–70 age group. Common comorbidities included hypertension (82%) and diabetes mellitus (76%). Levodopa-Carbidopa emerged as the most prescribed therapy (73%), followed by dopamine agonists (38%) and MAO-B inhibitors (22%). Polypharmacy was noted in 42% of cases, reflecting the complexity of treatment regimens in older adults. Non-motor symptoms such as cognitive impairment (54%), autonomic dysfunction (46%), and depression (38%) were prevalent, significantly impacting patient well-being. Medication adherence levels varied: 42% of patients demonstrated high adherence, 38% moderate, and 20% low adherence, primarily due to forgetfulness, regimen complexity, and financial issues. These findings underscore the need for a comprehensive, multidisciplinary approach in PD management for older people. Strategies such as patient education, caregiver support, and digital health technologies may enhance medication adherence and treatment outcomes. Furthermore, integrating non-pharmacological therapies and addressing socio-economic barriers are essential for holistic care. Future directions should focus on implementing personalized treatment plans, leveraging digital tools for real-time monitoring, and developing financial aid programs to reduce the burden of disease management. Overall, optimizing care for geriatric PD patients requires coordinated efforts to address the disorder's clinical and psychosocial aspects, ultimately improving their functional independence and quality of life.